Ablation of PDE4B protects from Pseudomonas aeruginosa‐induced acute lung injury in mice by ameliorating the cytostorm and associated hypothermia. Issue 9 (12th August 2021) - Abou Saleh, Lina; Boyd, Abigail; Aragon, Ileana V.; Koloteva, Anna; Spadafora, Domenico; Mneimneh, Wadad; Barrington, Robert A.; Richter, Wito
Abstract: Pseudomonas aeruginosa is a frequent cause of hospital‐acquired lung infections characterized by hyperinflammation, antibiotic resistance, and high morbidity/mortality. Here, we show that the genetic ablation of one cAMP‐phosphodiesterase 4 subtype, PDE4B, is sufficient to protect mice from acute lung injury induced by P aeruginosa infection as it reduces pulmonary and systemic levels of pro‐inflammatory cytokines, as well as pulmonary vascular leakage and mortality. Surprisingly, despite dampening immune responses, bacterial clearance in the lungs of PDE4B‐KO mice is significantly improved compared to WT controls. In wildtypes, P aeruginosa ‐infection produces high systemic levels of several cytokines, including TNF‐α, IL‐1β, and IL‐6, that act as cryogens and render the animals hypothermic. This, in turn, diminishes their ability to clear the bacteria. Ablation of PDE4B curbs both the initial production of acute response cytokines, including TNF‐α and IL‐1β, as well as their downstream signaling, specifically the induction of the secondary‐response cytokine IL‐6. This synergistic action protects PDE4B‐KO mice from the deleterious effects of the P aeruginosa ‐induced cytostorm, while concurrently improving bacterial clearance, rather than being immunosuppressive. These benefits of PDE4B ablation are in contrast to the effects resulting from treatment with PAN‐PDE4 inhibitors, which have been shown to increase bacterial burden and dissemination. Thus, PDE4B represents a promising therapeutic target in settings of P aeruginosa lung infections.